2011
DOI: 10.1208/s12249-011-9619-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioadhesive Microspheres for Bioavailability Enhancement of Raloxifene Hydrochloride: Formulation and Pharmacokinetic Evaluation

Abstract: Abstract. Raloxifene hydrochloride (R-HCl), a BCS class II drug, remains a mainstay in the prevention and pharmacologic therapy of osteoporosis. Its absolute bioavailability, however, is 2% due to poor solubility and extensive first pass metabolism. The present study describes two simultaneous approaches to improve its bioavailability, complexation of R-HCl with cyclodextrin(s), and formulation of mucoadhesive microspheres of the complex using different proportions of carbopol and HPMC. Microspheres were pale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Even though, 60% of raloxifene is absorbed orally, the absolute plasma bioavailability is only 2% because of its poor aqueous solubility (0.25 mg/lit in water) and extensive first pass metabolism by glucuronide conjugation [4]. RL-HCL comes under class II (low solubility and high permeability) of biopharmaceutical classification system (BCS) with lesser bioavailability [5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though, 60% of raloxifene is absorbed orally, the absolute plasma bioavailability is only 2% because of its poor aqueous solubility (0.25 mg/lit in water) and extensive first pass metabolism by glucuronide conjugation [4]. RL-HCL comes under class II (low solubility and high permeability) of biopharmaceutical classification system (BCS) with lesser bioavailability [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Even though several research works are being carried out to enhance the solubility and bioavailability of raloxifene by formulating it as tablets [19], microemulsions [20], microspheres [5], transdermal patch [21], and polymeric nanoparticles [22], still it is required to design the formulation having combined advantages like sustained release and avoiding first pass metabolism of RL-HCL. Therefore, the aim of the present work is to improve the bioavailability of RL-HCL by formulating it as SLN.…”
Section: Introductionmentioning
confidence: 99%
“…it has low solubility and high permeability. But the bioavailability of raloxifene is very low, only 2%, due to a high first-pass metabolism in the liver by glucuronidation and enterohepatic cycling (Jha et al, 2011). So it would be advantageous to increase the solubility of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…So it would be advantageous to increase the solubility of the molecule. Raloxifene is available in HCl salt form as raloxifene (RLX; Rai et al, 2010;Jha et al, 2011). This drug is poorly absorbed from the gastrointestinal (GI) tract.…”
Section: Introductionmentioning
confidence: 99%
“…Trials encompassed use of hydrophilic binders, 9 cogrinding technique, 10 cyclodextrin complexation, 8 and use of mucoadhesive microspheres of the complex to give a controlled release pattern. 11 Although the reported permeability of RLX as class II drug is high, one attempt has adopted enhancing in vitro intestinal permeability of drug via microemulsion technique and a water titration method. 12 Nevertheless, the authors recommended that their in vitro assumptions could only be confirmed after in vivo animal experimentation, which they did not perform.…”
Section: Introductionmentioning
confidence: 99%